Reforging kinship bonds with older people - Calleja, Carlo (Magyar Gerontológia, 2024)
In this paper I start with a provocative claim that a society is being constructed that creates - while simultaneously disposing of - older men and women. I argue that Western contemporary society is creating an environment that is increasingly hostile to older persons.